Family forms of accommodation for elderly and disabled persons as an innovative form of social care in Ukraine - Ільчук, Л. І. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2017)
An alternative forms and methods of social work with elderly and disabled persons examined in the article. International social practice on the key family forms of the residence for elderly and disabled persons has been investigated. The following public and social (transitional) forms of accommodation for elderly persons are revealed: family nursing home; temporary foster families for elderly persons; patronage families. The attention is focused on the foster and patronage families, as an effective tool in work with the elderly and disabled persons. Types of the foster families for an elderly person proposed.